Total reaction and fusion cross sections at sub- and near-barrier energies for the system $^7$Li + $^{28}$Si - A. Pakou; K. Rusek; N. Alamanos; Aslanoglou, X.; Kokkoris, M.; A. Lagoyannis; Mertzimekis, T.; Musumarra, A.; Nicolis, N.; Pierroutsakou, D.; Roubos, D. (Eur. Phys. J. A, 2009)
Abstract  Fusion cross sections are extracted for the $^7$Li + $^{28}$Si system, via reaction cross section and transfer measurements at sub- and near-barrier energies ( E$_{lab}$ = 5.7 to 14 MeV). The energy evolution of transfer to reaction cross section ratios is determined with the aid of CDCC calculations, which subsequently allows the deduction of fusion cross sections at sub- and near-barrier energies. It is shown that fusion can be well represented in a BPM context. Fusion cross sections are compared for the systems $^7$Li + $^{28}$Si and $^6$Li + $^{28}$Si, the latter studied previously, and are found to exhibit different strengths. Last, the direct channels determined at 13 MeV, are found to be dominated by a 2n-transfer mechanism.